The Correlation between Reading Anxiety and Students' Critical Reading Ability at English Department of UNP - Erdiana Erdiansyah; Fitrawati Fitrawati (Universitas Negeri Padang, 2023)
This study investigates the possible relationship between reading anxiety and the critical reading ability of students majoring in English. Thirty-two students majoring in English education were selected as the research sample. The instrument used by the researcher was the form of a TOEFL test consisting of 30 questions which were used to measure students' ability to read critically. In addition, the researcher also developed a questionnaire based on the theory of experts consisting of 20 statements used to measure students' reading anxiety. Pearson Product-Moment investigates the relationship between reading anxiety and students' critical reading ability. This research found several results; 1) Most students experience anxiety at the intermediate level, with a percentage of 62.50%. 2) The level of students' critical reading ability is at the average level, with a percentage of (75%). 3) There is a relationship between students' reading anxiety and critical reading ability, as indicated by r = .0.375. This shows that H0 is rejected and Ha is accepted. The results imply that the higher or lower reading anxiety students experience, the lower or higher their scores in critical reading. In addition, there is a significant effect of reading anxiety on students' critical reading skills. Lastly, this research is expected to have implications for English teachers, students, and future researchers.